Here where the sunbeams are green - Phillips, Helen, 1981- (Delacorte, 2012)
Sisters Madeline and Ruby travel to a Central American jungle to help find their missing father, a renowned bird watcher, only to discover a nefarious plot that puts their lives in danger.